Klinik Penyusunan Instrumen Penelitian Guna Peningkatan Kualitas Skripsi Mahasiswa - Hasnawati Hasnawati; Khairun Nisa; Setiani Novitasari; Hikmah Ramdhani Putri (Universitas Mataram, 2026)
The quality of a student's thesis is highly dependent on the accuracy and appropriateness of the research instruments used. However, many final year students still experience difficulties in designing instruments that meet the requirements of validity, reliability, and suitability for research objectives, resulting in delays in completion and a decline in the quality of scientific work. This community service activity aims to provide practical assistance through the